An object model for dynamic mixins - Burton, Eden; Sekerinski, Emil (Computer languages, systems & structures, 2018)
•A statically typed language called mix is defined for dynamic mixin based development.•An object model used for its implementation avoids name lookup for finding method pointers.•Preliminary results indicate method access for dynamic mixins approaches the performance of applications using statically inherited classes. Dynamic mixins allow objects to be modified at runtime with modular extensions. In applications where method calls must traverse through multiple extensions, a performance penalty relative to static inheritance is realized as receivers of super-calls must be determined at run-time. This work describes an object model which significantly reduces this penalty. The approach is described in terms of a statically typed dynamic mixin-based language called ▪.